Poor Control of Plasma Triglycerides Is Associated with Early Decline of Estimated Glomerular Filtration Rates in New-Onset Type 2 Diabetes in China: Results from a 3-Year Follow-Up Study - Chuan Wang; Lingshu Wang; Kai Liang; Fei Yan; Xinguo Hou; Fuqiang Liu; Li Chen (Journal of Diabetes Research)
Objective. Diabetic kidney disease (DKD) is the most common cause of end-stage renal disease (ESRD). Even after strict control of obesity, hyperglycemia, and hypertension, some patients still progress rapidly. Previous studies suggested diabetic dyslipidemia might be one of the factors responsible for this high residual risk. This study aims to explore the impact of long-term lipid control on renal outcome in new-onset type 2 diabetes mellitus (T2DM). Methods. We conducted a 3-year follow-up study, involving 283 subjects with new-onset T2DM, and observed the effect of baseline and follow-up metabolic abnormalities, especially dyslipidemia, on the early damage of kidney function using multiple logistic regression analysis. Results. After 3 years follow-up, patients achieved a better control of body weight, hypertension, and blood glucose. The most reduced eGFR group shared the least reduced BMI and LDL-C, as well as the greatest increase in TG levels. Only TG in the follow-up, not any of the baseline data, nor obesity, blood glucose, BP, or LDL-C in the follow-up, was found to be significantly correlated with the most reduced eGFR. Compared with patients with constantly abnormal TG levels, the risks were even higher in the subjects who experienced a transition from normal TG to hypertriglyceridemia (OR=2.576 versus OR=2.184, after multiple adjustment), and by tight controlling of TG, patients started with abnormal baseline TG levels could reduce the risk of DKD progression to the same low levels as the TG-constantly-normal group. Conclusion. This study emphasized the importance of long-term TG control in East Asian patients with new-onset T2DM: TG control can delay the decline of kidney function in the early stage of DKD, and reversal of hypertriglyceridemia may undo the risks of the past. It is time to pay more attention to the control of TG in new-onset T2DM.